(untitled) (Journal of Legal Studies, 2018)
The taxation of non – resident economic entities supposes the establishment of an administrative framework as fair, efficient, effective and comprehensible as possible, fact due to the multifaceted nature of the concept of profits generated by an enterprise and which depend on some items as: the foundation of incomes sources, the methods of valuation and collecting taxes, as well as different rules of establishment of some tax thresholds in different situations. Taking into account the legal doctrine, as well as jurisprudence, respectively the national and international tax practices, we can notice the fact that the profits of enterprises are founded, stricto sensu, on tax declarations made by companies. Therefore, we consider very important, in this way, the technical capability of tax administrations regarding the establishment, implementation and coordination of some good practice procedures. In this article, we have tackled the treatment regarding the taxation of non – resident economic entities in Romania. The first part of the paper represents a truth caveat in which is presented and analysed the international and European theoretical framework of legal and tax treatment of non – resident economic entities. The second part of the paper represents a quid pro quo of taxing of non – resident economic entities in Romania, in which are analyzed the taxing stipulations established on national level. The final part of the article is enriched with the presentation and analysis of a particular case regarding the taxation of non – resident economic entities in Romania. The conclusion resulted from this article highlights the fact that Romania had made important steps regarding â€•the adjustmentâ€– of national tax legislation, as well as the permanent improving of tax administration framework in the field of non – resident economic entities taxation in Romania.